2021
DOI: 10.1108/meq-10-2021-0240
|View full text |Cite
|
Sign up to set email alerts
|

Can labor productivity growth reduce carbon emission? Evidence from OECD countries and China

Abstract: PurposeThe purpose of this study is to examine the challenges involved in the trade-offs of labor productivity and per capita carbon dioxide (CO2) emission.Design/methodology/approachIn this research, we used a balanced dataset of 36 OECD countries and China between 1990 and 2018. We examined the relationship between labor productivity and per capita CO2 emission for OECD countries and China based on an Environmental Kuznets Curve (EKC) hypothesis. Further, the fixed effects model of estimation was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…The results of the fixed effect regression support the argument that economic growth significantly affected and enhanced emissions of CO 2 . In addition, the study in contrast to Chen et al (2022) found no link or support for the EKC hypothesis.…”
Section: Literature Reviewcontrasting
confidence: 80%
See 1 more Smart Citation
“…The results of the fixed effect regression support the argument that economic growth significantly affected and enhanced emissions of CO 2 . In addition, the study in contrast to Chen et al (2022) found no link or support for the EKC hypothesis.…”
Section: Literature Reviewcontrasting
confidence: 80%
“…Following the works of Chen et al (2022), we use labor productivity as a proxy of economic activity instead of the widely used per capita GDP. The widely used indicate i.e.…”
Section: The Econometric Modelsmentioning
confidence: 99%
“…The effects of labor productivity on CO 2 emissions have been less extensively studied. Fitzgerald et al ( 2018 ) and Chen et al ( 2021 ) study the trade-off of CO 2 emissions per capita and labor productivity based on EKC hypothesis and a fixed effects model in 36 OECD countries and China during the period 1990–2018. Their results confirm the N-shaped EKC suggesting that at the early development stage, CO 2 emissions increase with labor productivity (positive relation), and after a certain threshold, CO 2 emissions decrease with rising labor productivity (negative relation), and later, the CO 2 emissions return to increasing trend with higher labor productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As one of the major emerging countries (Lin and Wang 2020), China has witnessed remarkable economic expansion in the past few decades (Chen and Zheng 2023). However, this growth has also been accompanied by significant environmental challenges (Su and Fan 2022), such as rapid resource depletion and severe environmental pollution (Chen et al 2022). China has established goals for green development to address these issues and tackle global environmental challenges like climate change (Zhu et al 2019).…”
Section: Introductionmentioning
confidence: 99%